The impact of performance expectancy on purchasing travel products via online travel agents websites: gender as moderator / Safwan Marwin Abdul Murad ... [et al.] - Abdul Murad, Safwan Marwin; Sivapathy, Arunnaa; Mohd Nor, Annuar Aswan (Universiti Teknologi MARA, Kedah, 2021)
Online travel purchasing can be made via online travel agents' websites (OTAs). While online travel agents (OTAs) keep leveraging their services to various segments of the travel and tourism industry, OTAs face a great problem of consumers' rejection from purchasing directly via their websites. Therefore, OTAs are striving to remain sustainable and profitable in the highly competitive online travel market. To mitigate this challenge, OTAs need to serve their customers by offering them superior service performance to attract them to purchase via their platform. This calls for a thorough understanding of the performance or usefulness factors related to the OTA context. Attempted to fill this gap, this study aims to investigate the relationship between performance expectancy and customer intention to purchase travel products via OTAs websites. By using Unified Theory of Acceptance and Use of Technology (UTAUT) as a base model, this study also examined the moderating role of gender in affecting the relationship between performance expectancy and purchase intention. The findings show that performance expectancy has positive effect on intention to purchase tourism products via OTAs websites. However, gender is found to have no moderation effect on the relationship between performance expectancy and purchase intention.